KEPEDULIAN PERUSAHAAN TERHADAP LINGKUNGAN - Ronny Hendrawan; Samsul M (Fakultas Seni Rupa dan Desain ITB, 2007)
The existence of high-tech corporations in villages are regarded as aliens in their environment. This indicates a wide gap between them and the environments. That gap may result in an interaction that tends to be negative. Although this has been anticipated by the initiators implemented in Amdal document accompanied by UPL & UKL, it cannot guarantee that it can give a solution of the gap. Any efforts to bridge the gap through CD that turn into CSR do not have a strong foundation by law or academically. However, CSR is a way to develop collaboration between Academics (A), Businessmen (B) and Government (G). The attempts to combine the ABG concept have several obstacles either from the internal or from external institutions. The corporations' care for environment, well-known as CSR, can be regarded as a new breakthrough to provide a chance for developing creativity, not only in developing society, research, and community service but also in improving the roles of government for public service, especially in managing environment. It can also reposition the roles of government in society, as it was proposed by Al Gore.